An analysis of approximate controllability for Hilfer fractional delay differential equations of Sobolev type without uniqueness - Johnson, Murugesan; Kavitha, Krishnan; Chalishajar, Dimplekumar; Malik, Muslim; Vijayakumar, Velusamy; Shukla, Anurag (Nonlinear Analysis: Modelling and Control, 2023)
This study focused on the approximate controllability results for the Hilfer fractional delay evolution equations of the Sobolev type without uniqueness. Initially, the Lipschitz condition is derived from the hypothesis, which is represented by a measure of noncompactness, in particular, nonlinearity. We also examined the continuity of the solution map of the Sobolev type of Hilfer fractional delay evolution equation and the topological structure of the solution set. Furthermore, we prove the approximate controllability of the fractional evolution equation of the Sobolev type with delay. Finally, we provided an example to illustrate the theoretical results.